STUDENTS’ PERCEPTION ON QUIZZIZ AS GAME BASED LEARNING IN LEARNING GRAMMAR IN WRITEN DISCOURSE - Fakhruddin, Afief; Nurhidayat, Eka (Wiralodra English Journal, 2020)
The study is entitled the students’ perception on Quizizz as Game Based Learning as a in learning grammar in Written discourse. The aimed of this research was to investigate students’ opinion on Quizizz as Game Based Learning as a in learning grammar in Written discourse and their obstacles in the implementation. The data for this study were gained through qualitative method that used questionnaire and interview, and the respondents were four semester students who used quizziz as their learning activity. And created 10 questions relevant to the topics which are students already learned before by using Quizizz as games based learning for 20 minutes before finishing grammar in written discourse class once the students feel very tired, sleeping and bored for their grammar in written discourse class. The study revealed that the students had positive perception on the use of quizziz, and all students were very active to answer the questions which provided by researches, and more concentrated on the topic. The result of the study expected to give contribution in improving EFL teaching and learning activity, especially in learning grammar in Written discourse.